Human Placenta‐Derived Mesenchymal Stromal‐Like Cells Enhance Angiogenesis via T Cell‐Dependent Reprogramming of Macrophage Differentiation. (14th March 2017) - He, Shuyang; Gleason, Joseph; Fik‐Rymarkiewicz, Ewa; DiFiglia, Andrea; Bharathan, Mini; Morschauser, Andrew; Djuretic, Ivana; Xu, Yan; Krakovsky, Michael; Jankovic, Vladimir; Buensuceso, Charito; Edinger, James; et al.
Abstract: Peripheral arterial disease (PAD) is a leading cause of limb loss and mortality worldwide with limited treatment options. Mesenchymal stromal cell (MSC) therapy has demonstrated positive effects on angiogenesis in preclinical models and promising therapeutic efficacy signals in early stage clinical studies; however, the mechanisms underlying MSC‐mediated angiogenesis remain largely undefined. Here, we investigated the mechanism of action of human placenta‐derived MSC‐like cells (PDA‐002) in inducing angiogenesis using mice hind limb ischemia model. We showed that PDA‐002 improved blood flow and promoted collateral vessel formation in the injured limb. Histological analysis demonstrated that PDA‐002 increased M2‐like macrophages in ischemic tissue. Analysis of the changes in functional T cell phenotype in the draining lymph nodes revealed that PDA‐002 treatment was associated with the induction of cytokine and gene expression signatures of Th2 response. Angiogenic effect of PDA‐002 was markedly reduced in Balb/c nude mice compared with wild type. This reduction in efficacy was reversed by T cell reconstitution, suggesting T cells are essential for PDA‐002‐mediated angiogenesis. Furthermore, effect of PDA‐002 on macrophage differentiation was also T cell‐dependent as a PDA‐002‐mediated M2‐like macrophage skewing was only observed in wild type and T cell reconstituted nude mice, but not in nude mice. Finally, we showed that PDA‐002‐treated animals had enhanced angiogenic recovery in response to the second injury when PDA‐002 no longer persisted in vivo. These results suggest that PDA‐002 enhances angiogenesis through an immunomodulatory mechanism involving T cell‐dependent reprogramming of macrophage differentiation toward M2‐like phenotype. Stem Cells 2017;35:1603–1613 Abstract : PDA‐002 promotes M2‐LIKE macrophage differentiation in unilateral HLI model in db/db mice. (A‐B) Representative images of CD68+(green) Arg1+(red) DAPI+ (blue) macrophages in vehicle and PDA‐002 treated animals 14d post‐HLI. Scale bar, 10μm. (C) Quantification of CD68+ macrophages in the thigh 7, 14 and 28d post‐HLI (n = 4). (D) Quantification of CD68+Arg1+ macrophages in the thigh 7, 14 and 28d post‐HLI (n = 4). All graphs show mean ± s.e.m. *, p < 0.05; **, p < 0.01; ***, p < 0.005. N = number of animals.